2017
DOI: 10.1136/bmjopen-2017-016030
|View full text |Cite
|
Sign up to set email alerts
|

Progression of disease preceding lower extremity amputation in Denmark: a longitudinal registry study of diagnoses, use of medication and healthcare services 14 years prior to amputation

Abstract: ObjectivesPatients with non-traumatic lower extremity amputation are characterised by high age, multi-morbidity and polypharmacy and long-term complications of atherosclerosis and diabetes. To ensure early identification of patients at risk of amputation, we need to gain knowledge about the progression of diseases related to lower extremity amputations during the years preceding the amputation.DesignA retrospective population-based national registry study.SettingThe study includes data on demographics, diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 44 publications
(43 reference statements)
2
33
1
Order By: Relevance
“…66 A recent Danish study analyzing level of amputation and the risk of mortality found that more proximal amputations were associated with a higher risk of death. 39 In our work, we did not find higher amputation rates following proximal revascularizations-rather the opposite, even though these associations disappeared when we adjusted for comorbidities. A more proximal revascularization might rather be a surrogate measure of a more widespread atherosclerotic disease.…”
Section: Commentscontrasting
confidence: 51%
“…66 A recent Danish study analyzing level of amputation and the risk of mortality found that more proximal amputations were associated with a higher risk of death. 39 In our work, we did not find higher amputation rates following proximal revascularizations-rather the opposite, even though these associations disappeared when we adjusted for comorbidities. A more proximal revascularization might rather be a surrogate measure of a more widespread atherosclerotic disease.…”
Section: Commentscontrasting
confidence: 51%
“…CLI was defined as the presence of rest pain or tissue loss (ICD-9-CM code 440. [22][23][24]. Major lower extremity amputation was defined as any amputation above the ankle joint (ICD9-CM: codes 84.…”
Section: Methodsmentioning
confidence: 99%
“…7,8 In Denmark, 30-day mortality has been reported to be 16% to 35% and 1-year mortality to be 37% to 59% [9][10][11] in this frail group of patients. They suffer from long-term complications of atherosclerosis and diabetes resulting in ischaemia and infected and necrotic wounds.…”
Section: Introductionmentioning
confidence: 99%
“…They suffer from long-term complications of atherosclerosis and diabetes resulting in ischaemia and infected and necrotic wounds. 7,8 In Denmark, 30-day mortality has been reported to be 16% to 35% and 1-year mortality to be 37% to 59% [9][10][11] in this frail group of patients.…”
Section: Introductionmentioning
confidence: 99%